PELATIHAN MENINGKATKAN MINAT BACA SISWA MELALUI GERAKAN LITERASI SEKOLAH DI SDN 3 PENATIH DENPASAR - I Komang Sukendra; Putu Dessy Fridayanthi; Gusti Ayu Made Puspawati; Ida Ayu Agung Ekasriadi (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2024)
The School Literacy Movement is a comprehensive effort to make schools a learning organization whose citizens are literate throughout life through public involvement. The Education Department is trying to improve students' literacy and numeracy skills in schools, but there are still many students who have little interest in reading so their literacy is low. This service aims to increase students' interest in reading through school literacy movement activities involving class IV and class V students at SDN 3 Penatih, East Denpasar District, Denpasar City. This activity was carried out in conjunction with the 2023 Thematic Real Work Lecture for students conducted by lecturers at PGRI Mahadewa Indonesia University. This activity method uses training and mentoring. There are two training activities that are effective in increasing students' interest in reading. namely book review activities and writing book reviews carried out to analyze and understand the books students read. The next activity is a book discussion group used to encourage students to discuss and share their understanding of books. The results of community service training show that book review activities and book discussion groups have a significant impact in increasing students' interest in reading. With a literacy environment that stimulates and can motivate students, students' interest in reading at SDN 3 Penatih, Denpasar City increases significantly.